An intricate case of multidrug resistant Plasmodium falciparum isolate imported from Cambodia - Raffaele Dell’Acqua; Claudia Fabrizio; Francesco Di Gennaro; Sergio Lo Caputo; Annalisa Saracino; Michela Menegon; Mariangela L’Episcopia; Carlo Severini; Laura Monno; Francesco Castelli; Gioacchino Angarano (Malaria Journal, 2017)
Abstract Background Imported cases of multidrug resistant Plasmodium falciparum and treatment failure with artemisinin-based regimens, although rare, have been described also in Western countries and their management is often challenging. This is also due to an inadequate knowledge and implementation of health prevention measures. Case report A complex case of imported malaria caused by Plasmodium vivax/P. falciparum isolates in a patient who was not taking chemoprophylaxis while he was travelling in Cambodia is reported in this article. After failures of artemisinin-based and both oral and intravenous quinine-based regimens, a multidrug resistant P. falciparum was detected. The patient was successfully treated with atovaquone–proguanil. Conclusions This experience highlights the importance of a careful management that should be based not only on the most up-to-date guidelines, but also on the awareness of a rapidly evolving scenario.